Mining exports, direct and indirect taxes and their incidence in the tax collection of the Cnetral Gobernment: 2017-2019 - Villa Morocho, Eduardo (2019)
Objective: To relate how commodity exports impact to the tax revenues of the Central Government and the type of relationship that exists between direct and indirect taxes. Method: The type of research is correlational descriptive method was applied, structuring a correlation matrix and regression lines, for that was applied an official data from SUNAT, INEI, BCRP. Results: The study shows the greatest contribution of the IGV in tax collection, followed by income tax, but due to the degree of correlation reached, this last tax has a bigger incidence on tax collection. However, to contrast the mining exports with the direct taxes, it appreciates a weak and negative dependence relationship, in which it implies that the tax collection is weakly affected by the mineral exports. Conclusions: It concludes, by the grade and type of correlation obtained, that the increase in mining exports does not exert bigger changes in tax collection being the inverse type impact.